Effect of the period of resting in elite judo athletes: Hematological indices and copper/zinc-dependent antioxidant capacity - Koury, J. C.; de Oliveira, C. F.; Portella, E. S.; Junior, A.; Donangelo, C. M. (Biological Trace Element Research, 2005)
The purpose of this study was to evaluate the effect of the resting period on hematological and copper-zinc-dependent antioxidant indices in Brazilian elite judo athletes (n = 7). Venous blood samples were collected after 24-h and 5-d periods of resting following a competition, with an interval of 30 d between collections. Two months prior to and during the study, each athlete received an individualized adequate diet. Body composition was determined at both study periods. The following were analyzed: in whole blood, hemoglobin, hematocrit, red cell count, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, red cell distribution width, and white cell count; in plasma, zinc, copper, iron, ceruloplasmin, and total iron-binding capacity; in erythrocytes, metallothionein, copper/zinc superoxide dismutase, and osmotic fragility. Dietary intake and body composition did not affect the biochemical measurements. A significant reduction in ceruloplasmin and superoxide dismutase activity was found after 5 d compared to 24 h of resting. A significant correlation between erythrocyte metallothionein and red cell distribution width was observed after 24 h of resting (r = -0.83, p = 0.02), whereas positive correlations of metallothionein with hemoglobin, red cell count, and mean corpuscular hemoglobin concentration were observed after 5 d of resting (r = 0.76, p = 0.05). Our results suggest that a longer resting period favors homeostatic adjustments in the erythrocyte population and in the copper/zinc-dependent antioxidant system in elite judo athletes.